Assessment of the Effectiveness of Investment Strategy in Solar Photovoltaic (PV) Energy Sector: A Case Study. (May 2017) - Zhang, Xingxing; Shen, Jingchun; Yang, Tong; Tang, Llewellyn; Wu, Yupeng; Pan, Song; Wu, Jinshun; Xu, Peng
Abstract: Solar photovoltaic (PV) energy is now promising to offer potential solutions for sustainable development, especially in China. A representative Chinese solar PV manufacturer - Shunfeng International Clean Energy Limited (SFCE) - is therefore assessed in this paper, including (1) investment strategies in China's recent macroeconomic exposure; (2) the market exposure and vulnerability. The macroeconomic challenges in case of China's continuous GDP growth would have significant implications for SFCE's investment strategy. Although SFCE's vulnerability is high, it has mediated its macro exposure and protect itself by advanced non-pricing competition, product/service differentiation, vertical and horizontal integration, and high-profit diversification etc. The research result is expected to offer useful indications for solar PV companies to adapt and succeed in the future energy industry and simultaneously help the world to mitigate climate change.